THE INFLUENCE OF WORKLOAD, WORK ENVIRONMENT AND TEAMWORK AGAINST TURNOVER INTENTION WHICH MEDIATED THROUGH ORGANIZATION COMMITMENT (CASE STUDY ON EMPLOYEE AT PT. MULTIPRO JAYA PRIMA) - Hidayah, Nurul; Chaerudin, Chaerudin (Dinasti International Journal of Management Science, 2020)
This research aimed to measure and analyze those influence which came from workload, work environment and teamwork on turnover intention through organization commitment. This research include in quantitative research. Population and sample in this research were all employee at PT. Multipro Jaya Prima, with total 84 employees. The sample gathered technique used saturated sampling. The research data used linear regression. The results from t-test for variables such as workload, work environment, and teamwork had an influence toward turnover intention either partially or simultaneously.